Anatomical and Radiological Considerations When Colonic Perforation Leads to Subcutaneous Emphysema, Pneumothoraces, Pneumomediastinum, and Mediastinal Shift - Abdalla, Sala (Surg J (N Y), 2018)
While colonoscopy is generally regarded as a safe procedure, colonic perforation can occur and the risk of this is higher when interventional procedures are undertaken. The presentation may be acute or delayed depending on the extent of the perforation. Extracolonic gas following colonic perforation can migrate to several body compartments that are embryologically related and it has previously been reported in the thorax, mediastinum, neck, scrotum, and lower limbs. This review discusses in detail the anatomical pathways that led to a rare case of widespread subcutaneous emphysema, bilateral pneumothoraces, pneumomediastinum, and mediastinal shift from colonic perforation during a diagnostic colonoscopy. This is further supported by a description of the radiological images.